HISTOGRAM (History In Hologram): Fun Learning Media to Learn Ancient Relics of Indonesia - Dimas Aditia; Soni Ariatama; Amar Ma’ruf (Pancaran Pendidikan, 2020)
Archaeological objects are historical relics that have important values for human life. But not every student can see and feel the atmosphere of ancient objects, because they have long been extinct or maintained their existence. The introduction of ancient objects through the media in the form of images contained in books, two-dimensional drawings and other teaching aids, this is considered ineffective because two-dimensional picture can only be seen on one side only, but by using 3D Hologram technology it is expected that in learning it can make historical lessons about ancient objects can be more interesting and enjoyable as well as helping in introducing efforts to conserve ancient objects. The results of this research are expected to be able to provide 3D Hologram technology by utilizing the principles of holographic work that is able to provide convenience for student by their own gadget.